Edukasi Peningkatan Self Control terhadap Perilaku Seks Bebas pada Remaja di SMA Muhammadiyah Kota Langsa - Nanda Mirani; Maulida; Nala Ramadhani (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
Free sex behavior is contrary to national culture. However, in fact, based on several research data, it shows that the free sex behavior of teenagers in Indonesia is quite worrying. In Indonesia, there are about 4.5% of boys and 0.7% of girls aged 15-19 years who claim to have had premarital sex. This community service activity is in the form of providing health education through counseling teenagers about free sex behavior. The results obtained from this community activity before the counseling was carried out, the majority of participants' knowledge was in the sufficient category, namely 46%, participants with less knowledge were 37% and only 17% of participants had good knowledge about free sex behavior. Health education about free sex was carried out with the help of power point media, during the activity the participants seemed interested in listening to the counseling given. The conclusion that can be drawn from this community service activity is that the participants are active and enthusiastic to take part in the counseling activities provided and are able to answer the questions given. The results of the evaluation showed that the participants understood the material presented, this indicated an increase in the participants' knowledge about free sex behavior.